Study in Step by Step Electric Energy Meter Connection Detection Method - Qing Zhiming; Fu Wang; Fei Wenli (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Electric energy meter wiring error variety, detection method and circuit can only detect some kinds of wrong wiring at present, as the current transformer and current detection unit terminal short-circuit characteristics of conventional methods in existence, not take out stitches under the premise of not achieving detection. Based on this, this paper puts forward a step detection method, detection circuit of voltage and current lines one by one through right off and polarity of current, gradually show every junction point junction and the fault point. Through the Multisim software simulation, and developed a set of wire detecting device, simulation and experimental results prove that the method is correct. Compared with conventional methods, can be more comprehensive and faster connection detection fault location. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7662